Improvement of CMAS resistance of laser glazed and nano-modified YSZ thermal barrier coatings - Avci, Ali; Karabas, Muhammet; Eker, Aysegul Akdogan; Akman, Erhan; Aslan, Caner (ELSEVIER SCI LTD, 2024)
The present investigation used atmospheric plasma spray (APS) as a method for the production of thermal barrier coatings composed of Yttria-stabilized zirconia (YSZ). A CO2 laser was used to remove surface cracks from the YSZ coatings' surface. Several parameter variations were applied to generate laser-glazed tracks on the coating surface, resulting in an impure surface microstructure with excellent surface properties. Scanning electron microscopy was utilized to analyse the tracks' microstructure. The optimal laser parameters were determined to be 77.7 W laser power, 215 mm laser distance, and, 120 mm s(-1) scanning speed based on microstructural characteristics. Once the laser parameters had been optimized, a whole coating surface was laser glazed. In order to ascertain the impact of laser glazing, stability analysis, fracture toughness, and hardness evaluations were conducted on both unglazed and laser-glazed coatings. The growth of a network of cracks was seen on the surface. The surface roughness exhibited a reduction of about tenfold in comparison to the unglazed YSZ. The presence of the monoclinic ZrO2 phase within the coating structure was successfully eradicated. The laser glazing process resulted in enhancements to both the fracture toughness and surface hardness of the coating. Despite the fact that the gaps and imperfections on the coating surfaces were repaired during laser glazing, some cracked structures nonetheless appeared. Nano YSZ was deposited on laser-glazed surfaces by the electrophoretic method in order to eliminate cracks from laser-glazed surfaces. The experimental results obtained from conducting calcium-magnesium-alumina-silicate (CMAS) and hot corrosion tests on laser-glazed coatings indicate that the use of nano YSZ filler leads to a significant reduction in salt penetration during both glassy melt and hot corrosion processes.
Keywords: Laser processing; YSZ; Surface modification; EPD; Thermal barrier coating; HOT CORROSION BEHAVIOR; SHOCK RESISTANCE; SURFACE; COMPOSITE; MICROSTRUCTURE; OXIDATION; Materials Science